Political parties as «schools of State life» - Azzolini, Giulio (International Gramsci Journal, 2025)
Gramsci redefined the concept of parties by broadening their semantic scope, historicizing their emergence, and identifying their essential functions. He argued that parties are critical mechanisms for guiding and educating society, fostering collective and universal goals while overcoming narrow group interests. Gramsci emphasized the interplay between political parties and the State, viewing parties as both embryonic State structures and instruments for shaping societal consensus. Moreover, he analyzed the risks of bureaucratization and elitism within party organizations, especially under authoritarian regimes. By examining the historical and sociopolitical contexts of Italy and Europe, Gramsci illustrated how parties have influenced modern political systems and social transformations. His insights underline the dual role of parties in guiding political participation and maintaining political order. This research highlights Gramsci’s enduring significance for understanding the dynamics of political organization and democratic theory.